Cortisol Analysis of Pterygoplichthys pardalis from Ciliwung River - Zhafirah, Adienda Yoesmah; Puspitasari, Riris Lindiawati (Universitas Muhammadiyah Surakarta, 2020)
The existence of Pterygoplichthys pardalis as one Loricariidae species were introduced to Indonesia and dominated the Ciliwung River. The high contaminant in Ciliwung River can lead to high stress levels so that fish experienced a decline due to the death or failure to reproduce. But not entirely external stressors affect the existence Pterygoplichthys pardalis. P. pardalis stress levels need to determined the adaptive mechanism polluted environment through the concentration of the hormone cortisol. This study was conducted to identify the level of stress P. pardalis based on concentration of the hormone cortisol. The method used a sample of fish raised in tank and fish from the river. Fish plasma will be analyzed using the ELISA method measure the cortisol. The higher concertration of cortisol showed more stress in Ciliwung fish. Based on the statistic result showed the significance value between two groups was 0.012 (sig<0.05). This assumed were difference cortisollevel between fish from tank and river. The results show that P. pardalis collected from river have higher concentrations of the cortisol than from tank. The cortisol level was 113.06 ng / ml.